Is there a synergic effect of propafenone associated with atrial overdrive pacing for atrial arrhythmia prevention? A randomised crossover study. Issue 2 (1st February 2000) - Garrigue, S; Barold, S S; Cazeau, S; Hocini, M; Jais, P; Haissaguerre, M; Clementy, J
Abstract : OBJECTIVE: To assess the effect of adding propafenone to atrial overdrive for the prevention of atrial arrhythmia episodes in patients with DDD pacemakers. DESIGN: 22 patients (8 female, 14 male, mean (SD) age 67 (9) years, range 48 to 77) with DDD pacemakers and frequent paroxysmal atrial arrhythmia episodes were evaluated in a randomised crossover study. SETTING: University hospital. METHODS: Atrial overdrive was defined as a paced rate of 10 paced beats/min above the mean ventricular rate stored for the last 24 hours in the pacemaker memory function. The protocol consisted of two phases of one month each. The first phase consisted of atrial overdrive alone, while in the second phase, propafenone (600 mg/day) was added to atrial overdrive (atrial overdrive + propafenone). All 22 patients underwent the two phases in random order. RESULTS: Mean ventricular rate was 72 (8) beats/min with atrial overdrive v 73 (6) with atrial overdrive + propafenone (NS). With atrial overdrive, 14 patients (64.6%) had no recorded atrial arrhythmia v 15 (68.2%) with atrial overdrive + propafenone (NS). There was no statistical difference between the atrial overdrive and atrial overdrive + propafenone phases with regard to the number of atrial arrhythmia episodes (14 (27) v 13 (28)), their total duration (30 (78) v 29 (63) h), and their maximum duration (41 (72) v 31 (58) min). However, in the brady-tachy subgroup with persistent atrial arrhythmias, atrial overdrive + propafenone produced a shorter mean cumulative duration of atrial arrhythmia than atrial overdrive (104 (115) v 178 (149) h, p = 0.04), with a significant decrease in the number of atrial arrhythmia episodes (134 (98) v 102 (83), p = 0.05). The proportion of asymptomatic atrial arrhythmia episodes increased only in the AV block group during atrial overdrive + propafenone (p = 0.03). Three patients had atrial arrhythmias during atrial overdrive + propafenone but not with atrial overdrive alone. CONCLUSIONS: In DDD paced patients, the overall effect of propafenone during atrial overdrive is variable. Propafenone may increase the proportion of asymptomatic atrial arrhythmia episodes. A proarrhythmic effect of propafenone was documented (aggravation of atrial arrhythmias). These results need to be confirmed by further larger randomised studies.